AGN STORM 2. II. Ultraviolet Observations of Mrk 817 with the Cosmic Origins Spectrograph on the Hubble Space Telescope - Y. Homayouni; Gisella De Rosa; Rachel Plesha; Gerard A. Kriss; Aaron J. Barth; Edward M. Cackett; Keith Horne; Erin A. Kara; Hermine Landt; Nahum Arav; Benjamin D. Boizelle; Misty C. Bentz; et al. (The Astrophysical Journal, 2023)
We present reverberation mapping measurements for the prominent ultraviolet broad emission lines of the active galactic nucleus Mrk 817 using 165 spectra obtained with the Cosmic Origins Spectrograph on the Hubble Space Telescope. Our ultraviolet observations are accompanied by X-ray, optical, and near-infrared observations as part of the AGN Space Telescope and Optical Reverberation Mapping Program 2 (AGN STORM 2). Using the cross-correlation lag analysis method, we find significant correlated variations in the continuum and emission-line light curves. We measure rest-frame delayed responses between the far-ultraviolet continuum at 1180 Å and Ly α λ 1215 Å ( ${10.4}_{-1.4}^{+1.6}$ days), N v λ 1240 Å ( ${15.5}_{-4.8}^{+1.0}$ days), Si iv + ]O iv λ 1397 Å ( ${8.2}_{-1.4}^{+1.4}$ days), C iv λ 1549 Å ( ${11.8}_{-2.8}^{+3.0}$ days), and He ii λ 1640 Å ( ${9.0}_{-1.9}^{+4.5}$ days) using segments of the emission-line profile that are unaffected by absorption and blending, which results in sampling different velocity ranges for each line. However, we find that the emission-line responses to continuum variations are more complex than a simple smoothed, shifted, and scaled version of the continuum light curve. We also measure velocity-resolved lags for the Ly α and C iv emission lines. The lag profile in the blue wing of Ly α is consistent with virial motion, with longer lags dominating at lower velocities, and shorter lags at higher velocities. The C iv lag profile shows the signature of a thick rotating disk, with the shortest lags in the wings, local peaks at ±1500 km s ^−1 , and a local minimum at the line center. The other emission lines are dominated by broad absorption lines and blending with adjacent emission lines. These require detailed models, and will be presented in future work.